HARP Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The clinical and laboratory studies of an 11 year old girl with hypoprebetalipoproteinemia, acanthocytosis, retinitis pigmentosa and pallidal degeneration are reported from the Developmental and Metabolic Neurology Branch, National Institute of Neurological Disorders and Stroke and Clinical Pathology Department, National Institutes of Health, Bethesda, MD.